Evaluating the quality of health care by assessing patient satisfaction - Gabriela Ciolpan (CES Working Papers, 2019)
The performance of the healthcare system is obtained by evaluating the quality of the healthcare. The image obtained from health services assessments is important because it shows the degree to which they meet or exceed expectations. Attitudes towards health care are measured by the perception of patients through favorable or unfavorable responses to the care provided. The patient's satisfaction is obtained by evaluating his experience in healthcare, being concerned about the quality of the healthcare services. Between the quality of the medical services and the satisfaction of the patients there is a close connection, being a permanent challenge for evaluating the perception of the patients on the health services. Patient satisfaction represents their degree of satisfaction with their perception of a hospital quality management regarding the services provided by it and the results related to the health status, the interaction with the medical staff, having an impact on the evolution of their health status. Patients are increasingly responsible for managing their own health, and consumer information technologies are becoming a critical component of health systems. The methodological approach will be realized through a qualitative analysis through a prospective study, by reviewing the articles in the journals on identifying the particularities of the performance of a healthcare system. The performance of the health system can have a major influence on the national decision-makers to understand the characteristics and processes that contribute to the relative levels of performance.
Keywords: 330; patient satisfaction; patient attitudes; performance; health service evaluation